HBV‐RNA Co‐amplification May Influence HBV DNA Viral Load Determination. Issue 7 (26th May 2020) - Maasoumy, Benjamin; Geretti, Anna Maria; Frontzek, André; Austin, Harrison; Aretzweiler, Gudrun; Garcia‐Álvarez, Monica; Leuchter, Susanne; Simon, Christian O.; Marins, Ed G.; Canchola, Jesse A.; Cornberg, Markus; Delgado, Rafael; et al.
Abstract : Despite effective hepatitis B virus (HBV)‐DNA suppression, HBV RNA can circulate in patients receiving nucleoside/nucleotide analogues (NAs). Current assays quantify HBV DNA by either real‐time polymerase chain reaction (PCR), which uses DNA polymerase, or transcription‐mediated amplification, which uses reverse‐transcriptase (RT) and RNA polymerase. We assessed the effect of RT capability on HBV‐DNA quantification in samples from three cohorts, including patients with quantified HBV RNA. We compared the HBV‐DNA levels by real‐time PCR (cobas HBV, Roche 6800/8800; Xpert HBV, Cepheid), transcription‐mediated amplification (Aptima HBV, Hologic), and real‐time PCR with added RT capability (cobas HBV+RT). In the first cohort (n = 45) followed over 192 weeks of NA therapy, on‐treatment HBV‐DNA levels were higher with cobas HBV+RT than cobas HBV (mean difference: 0.14 log10 IU/mL). In a second cohort (n = 50) followed over 96 weeks of NA therapy, HBV‐DNA viral load was significantly higher with the cobas HBV+RT and Aptima HBV compared with the cobas HBV test at all time points after initiation of NA therapy (mean difference: 0.65‐1.16 log10 IU/mL). A clinically significant difference was not detected between the assays at baseline. In a third cohort (n = 53), after a median of 2.2 years of NA therapy, we detected HBV RNA (median 5.6 log10 copies/mL) in 23 patients (43.4%). Median HBV‐DNA levels by Aptima HBV were 2.4 versus less than 1 log10 IU/mL in samples with HBV RNA and without HBV RNA, respectively ( P  = 0.0006). In treated patients with HBV RNA, Aptima HBV measured higher HBV‐DNA levels than Xpert HBV and cobas HBV. Conclusion: Tests including an RT step may overestimate HBV DNA, particularly in samples with low viral loads as a result of NA therapy. This overestimation is likely due to amplification of HBV RNA and may have an impact on clinical decisions. Abstract :